1988
DOI: 10.1016/0304-3959(88)90139-x
|View full text |Cite
|
Sign up to set email alerts
|

Post-herpetic neuralgia: 208 cases

Abstract: Two hundred and eight patients with post-herpetic neuralgia (PHN) were assessed in a prospective, longitudinal study designed to evaluate demography, clinical features, treatment results and long-term status. PHN affected both sexes equally increasing in frequency and severity with age. There was a predilection for involvement of the ophthalmic division of the trigeminal nerve and for mid-thoracic dermatomes. The pain descriptors chosen reflected both steady and brief paroxysmal components in most patients. Sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0
4

Year Published

1992
1992
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(44 citation statements)
references
References 27 publications
1
39
0
4
Order By: Relevance
“…The following distinct clinical syndromes have been described [16,19,39,40,43,62,63]: encephalitis, myelitis, multifocal leukoencephalitis, ophthalmic zoster with contralateral hemiparesis, brainstem vascular syndrome (locked in syndrome) with herpes zoster in the upper cervical segments, cranial and peripheral nerve palsies, acute retinal necrosis, post herpetic neuralgia.…”
Section: Neurological Complications Of Herpes Zostermentioning
confidence: 99%
See 1 more Smart Citation
“…The following distinct clinical syndromes have been described [16,19,39,40,43,62,63]: encephalitis, myelitis, multifocal leukoencephalitis, ophthalmic zoster with contralateral hemiparesis, brainstem vascular syndrome (locked in syndrome) with herpes zoster in the upper cervical segments, cranial and peripheral nerve palsies, acute retinal necrosis, post herpetic neuralgia.…”
Section: Neurological Complications Of Herpes Zostermentioning
confidence: 99%
“…The antiviral therapy reduces the duration of viral shedding, limits the duration of new lesion-formation, accelerates the cutaneous healing and is superior to placebo in reducing the duration of postherpetic neuralgia [62,63]. All these 3 drugs are safe and well tolerated for short term administration.…”
Section: Treatmentmentioning
confidence: 99%
“…An early therapeutic approach using a low-dose capsaicin cream formulation to defunctionalize nerve endings in human skin required repeated daily applications over weeks [11]. Although pain arising from such topical capsaicin applications is mild, mucous membranes are highly sensitive to the effects.…”
Section: Introductionmentioning
confidence: 99%
“…Pain which persists beyond healing of the rash is one such definition (Watson et al, 1988), whereas others have suggested that only patients whose pain continues beyond some arbitrary cut-off point (such as 30 days or 2 months from rash onset) have PHN (Sauer, 1955;Eaglstein, Katz & Brown, 1970). Given its uncertain definition, estimates of the incidence of PHN have varied.…”
Section: The Clinical Picturementioning
confidence: 99%